2024
DOI: 10.1021/acsnano.3c11743
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Topologically Adaptable Solid Electrolyte Interphase for a Highly Reversible Zinc Anode

Tong Yan,
Sucheng Liu,
Jinye Li
et al.

Abstract: The performance of aqueous zinc metal batteries is significantly compromised by the stability of the solid electrolyte interphase (SEI), which is intimately linked to the structure of the electrical double layer (EDL) between the zinc anode and electrolyte. Furthermore, understanding the mechanical behavior of SEI is crucial, as it governs its response to stress induced by volume changes, fracture, or deformation. In this study, we introduce l-glutamine (Gln) as an additive to regulate the adsorbed environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In addition to the abovementioned polymeric materials, the application of organic small molecules has emerged as another effective approach for enhancing the electrochemical properties of the SEI layer. These organic small molecules, such as amino acids 118–122 and organic acids, 123 also provide high tunability in terms of chemical structure and functionality. In recent studies, amino acids have been shown to generally exhibit a high durability under harsh cycling conditions.…”
Section: Organic Materials For Interfacial Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the abovementioned polymeric materials, the application of organic small molecules has emerged as another effective approach for enhancing the electrochemical properties of the SEI layer. These organic small molecules, such as amino acids 118–122 and organic acids, 123 also provide high tunability in terms of chemical structure and functionality. In recent studies, amino acids have been shown to generally exhibit a high durability under harsh cycling conditions.…”
Section: Organic Materials For Interfacial Layersmentioning
confidence: 99%
“…For example, Yan et al introduced l -glutamine (Gln) as an additive to an aqueous Zn sulphate electrolyte. 118 This addition resulted in the in situ formation of a thin SEI layer composed of ZnS and Gln-related species. This SEI layer has a low modulus and hardness while possessing a high self-healing ability, which inhibits side reactions and dendrite growth at the anode surface (Fig.…”
Section: Organic Materials For Interfacial Layersmentioning
confidence: 99%
“…Aqueous Zn-ion batteries (AZIBs) have garnered significant interest as highly promising candidates for stationary energy storage systems due to their high cost-effectiveness, environmental benignity, and intrinsic safety. As an important foundation of AZIBs, Zn metal anodes have the advantages of a high theoretical volumetric capacity (5855 mAh cm –3 ), low redox potential (−0.76 V vs standard hydrogen electrode), atmospheric insensitivity, and abundant reserves. Nonetheless, challenges such as the propensity for dendritic failure and thermodynamic instability in aqueous environments for Zn metal anodes still hinder the commercial use of AZIBs. The limited nucleation sites and uneven deposition of Zn cause aggressive dendrite growth and “dead Zn”, which cause low Coulombic efficiency (CE) and even internal short-circuit failure of batteries. , Meanwhile, the spontaneous hydrogen evolution and parasitic corrosion on Zn anodes lead to the internal swelling and serious polarization of electrodes, drastically reducing the cycling life of AZIBs. , …”
Section: Introductionmentioning
confidence: 99%
“…The long-term cycling stability of the full cell was tested at a current density of 2.0 A g –1 , and the results are shown in Figure a. The negative-to-positive electrode capacity (N/P) ratio is 4.2, and a lower N/P ratio will favorably enhance the energy density of the battery (Supporting Information: additional N/P ratio details). The NB@Zn and CB@Zn electrodes exhibit characteristic discharge/charge curves and achieve high discharge capacities of 96.7 and 70.4 mAh g –1 after 1000 cycles, respectively, which also shows excellent performance in many excellent published articles (The list refers to reports from Table S1). ,, For the bare Zn battery, the discharge capacity of the full cell is low because of severe Zn dendrites and side reactions.…”
mentioning
confidence: 99%